A facile one-step method to produce MoS2 quantum dots as promising bio-imaging materials. Issue 30 (8th March 2016) - Liu, Qingqing; Hu, Chaofan; Wang, Xiaomin
Abstract : Fluorescent MoS2 quantum dots were prepared by solvothermal treatment of bulk MoS2 powders in the presence of NaOH. Abstract : A facile one-step, low cost and green method is developed to produce molybdenum disulfide quantum dots (MoS2 QDs) by solvothermal treatment in the presence of NaOH. The high resolution transmission electron microscope observation indicated the high crystallinity and narrow particle size distribution of the as-prepared MoS2 QDs. The as-prepared MoS2 QDs exhibited bright blue luminescence under UV light irradiation. Excitation-dependent photoluminescence emission is observed in the aqueous dispersion of MoS2 QDs. By being directly applied for bio-imaging of HeLa cells, MoS2 QDs showed bright luminescence, low toxicity and excellent biocompatibility. Furthermore, this convenient method may provide a potential advance for large-scale production of other layered materials.